Curriculum Innovation and Professional Competencies in Accounting Education: A Narrative Review - Hassanudin, Abdul Fatah (Summa : Journal of Accounting and Tax, 2025)
Curriculum reform in accounting education has become increasingly urgent amid digital disruption, sustainability imperatives, and global labor market demands. This narrative review synthesizes current literature from Scopus, Web of Science, and Google Scholar to identify effective strategies for reform. Four central themes emerge: the integration of digital competencies, the strengthening of employability and soft skills, the adoption of experiential learning methods, and the growing emphasis on ethics and sustainability. Findings show that digital literacy is strongly associated with work readiness, while interpersonal skills and ethical awareness are critical for long-term career success. Comparative evidence highlights regional disparities, with developed countries advancing more rapidly in digital and ethical integration than developing countries constrained by systemic barriers. These insights underline the importance of stronger academic–industry collaboration, supportive policy frameworks, and faculty development to drive effective reform. Ultimately, an integrated and multidimensional accounting curriculum is essential to prepare future accountants who are not only technically proficient but also adaptive, ethical, and socially responsible.